Study of three novel biomarkers, MR-proADM, midkine, and stromelysin2, and peripheral atherosclerosis in a Chinese Han population: A case-control study - Zhong Chen; Yawen Zhu; Lili Zhang (European Journal of Inflammation, 2020)
Midregional pro-adrenomedullin (MR-proADM), midkine, and stromelysin2 (ST2) are novel cardiac biomarkers associated with heart failure and atherosclerotic diseases like stable ischemic disease and acute coronary syndrome. The potential association between these three biomarkers and peripheral artery disease (PAD) remains unclear. The aim of this study was to assess the correlation between these three biomarkers and their association with PAD in the Chinese Han population. This study included 224 patients suspected of having coronary artery disease (CAD). All subjects underwent coronary angiography and carotid and subclavian ultrasound assessment for detection of coronary and peripheral atherosclerosis and were divided into two groups according to whether they had PAD or not. Pearson’s correlation coefficient r was calculated, and multivariable logistic regression analysis was conducted to represent the associations of these biomarkers and PAD. The study included 133 patients with PAD and 91 non-PAD controls and these two groups had similar values for age, ST2, hematocrit, hemoglobin, red blood cell counts, creatinine and CAD ratio, smoking, and type 2 diabetes (all p  > 0.05). Compared with non-PAD controls, patients with PAD had lower levels of MR-proADM and midkine and higher levels of TC, LDL-C, and fasting blood sugar (FBS) (all p  < 0.05). MR-proADM was positively and ST2 negatively correlated with midkine (all p  < 0.05). Compared with females, male patients had higher values of MR-proADM ( p  < 0.05) and similar levels of ST2 and midkine (all p  > 0.05). Multivariable regression analysis identified FBS as a risk predictor (OR: 1.163, 95% CI: 1.108–1.401, p  = 0.014) and MR-proADM as a protective factor (OR: 0.720, 95% CI: 0.529–0.920, p  = 0.037) of PAD. Three novel biomarkers, MR-proADM, midkine, and ST2, are internally related, and MR-proADM is gender-specific and a protective factor of peripheral atherosclerosis in the Chinese Han population studied. Clinical Trial: ChiCTR-DDD-17013908